Visualizing the ac magnetic susceptibility of superconducting films via magneto-optical imaging - Motta, M.; Colauto, F.; Zadorosny, R. [UNESP]; Johansen, T. H.; Dinner, R. B.; Blamire, M. G.; Ataklti, G. W.; Moshchalkov, V. V.; Silhanek, A. V.; Ortiz, W. A. (American Physical Society (APS), 2011)
We have established a link between the global ac response and the local flux distribution of superconducting films by combining magnetic ac susceptibility, dc magnetization, and magneto-optical measurements. The investigated samples are three Nb films: a plain specimen, used as a reference sample, and other two films patterned with square arrays of antidots. At low temperatures and small ac amplitudes of the excitation field, the Meissner screening prevents penetration of flux into the sample. Above a certain ac drive threshold, flux avalanches are triggered during the first cycle of the ac excitation. The subsequent periodic removal, inversion, and rise of flux occurs essentially through the already-created dendrites, giving rise to an ac susceptibility signal weakly dependent on the applied field. The intradendrite flux oscillation is followed, at higher values of the excitation field, by a more drastic process consisting of creation of new dendrites and antidendrites. In this more invasive regime, the ac susceptibility shows a clear field dependence. At higher temperatures a smooth penetration occurs, and the flux profile is characteristic of a critical state. We have also shown that the regime dominated by vortex avalanches can be reliably identified by ac susceptibility measurements. © 2011 American Physical Society.